The Effect Of Spiritual Leadership, Job Satisfaction, And Self-Efficacy On Employee Performance At The Ministry Of Religious Affairs Of Bengkulu Province - Radili, Putri; Irwanto , Tito; Prawitasari, Andriyani (Utami Publisher, 2025)
This study aims to determine the effect of spiritual leadership, job satisfaction, and work self-efficacy on employee performance at the Bengkulu Provincial Ministry of Religious Affairs. The sample in this study consisted of 61 employees at the Bengkulu Provincial Ministry of Religious Affairs who were civil servants. Data collection was conducted using questionnaires, and the analysis methods used were multiple linear regression, determination tests, and hypothesis tests. The regression analysis results show that Spiritual Leadership (X1), Job Satisfaction (X2), and Self-Efficacy (X3) have a positive effect on employee performance (Y). The coefficient of determination (R²) value of 0.698 indicates that the three variables are able to explain 69.8% of performance, while the remaining 30.2% is influenced by other factors not examined in this study. Based on the t-test results at a significance level of 0.05, each of the variables X1, X2, and X3 proved to have a significant partial effect on performance, because the significance value was below 0.05. In addition, the F-test results also showed that the three variables had a significant simultaneous effect on the performance of Village Office employees, indicated by a significance value of less than 0.05.